Effects of Land use Change on Coprini dung Beetles in Tropical Karst Ecosystems of Puluong Nature Reserve - Bac, Bui Van (VNU Journal of Science: Natural Sciences and Technology; Vol 35 No 4, 2019)
I examined variation in community structure, species richness, biomass and abundance of Coprini dung beetles from 45 trapping sites in meadows, 35-year-old secondary forests and primary forests in tropical, high-elevation karst ecosystems of Puluong Nature Reserve, Thanh Hoa Province. My main aim was to explore community response to the influence of land use change. By comparing the structure and community attributes of the beetles between 35-year-old secondary forests and primary forests, I expected to give indications on the conservation value of the old secondary forests for beetle conservation. Community structure significantly differed among land-use types. Species richness, abundance and biomass were significantly higher in forest habitats than in meadows. The cover of ground vegetation, soil clay content and tree diameter are important factors structuring Coprini communities in karst ecosystems of Pu Luong. The secondary forests, after 35 years of regrowth showed similarities in species richness, abundance and biomass to primary forests. This gives hope for the recovery of Coprini communities during forest succession. Keywords: Coprini, dung beetles, karst ecosystems, land use change, Pu Luong. References: [1] I. Hanski, Y. Cambefort, Dung beetle ecology, Princeton University Press, Princeton, 1991. [2] C.H. Scholtz, A.L.V. Davis, U. Kryger, Evolutionary biology and conservation of dung beetles, Pensoft Publisher, Bulgaria, 2009. [3] E. Nichols, S. Spector, J. Louzada, T. Larsen, S. Amezquita, M.E. Favila et al., Ecological functions and ecosystem services provided by Scarabaeinae dung beetles, Biol. Conserv. 141 (2008) 1461-1474. https://doi.org/10.1016/j.biocon.2008.04.011. [4] H.K. Gibbsa, A.S. Rueschb, F. Achardc, M.K. Claytond, P. Holmgrene, N. Ramankuttyf, J.A. Foleyg, Tropical forests were the primary sources of new agricultural land in the 1980s and 1990s, Proc Natl Acad Sci USA 107 (2010) 16732-16737. https://doi.org/10.1073/pnas.0910275107. [5] L.D. Audino, J. Louzada, L. Comita, Dung beetles as indicators of tropical forest restoration success: is it possible to recover species and functional diversity? Biol. Conserv. 169 (2014) 248-257. https://doi.org/10.1016/j.biocon.2013.11.023. [6] W. Beiroz, E.M. Slade, J. Barlow, J.M. Silveira, J. Louzada, E. Sayer, Dung beetle community dynamics in undisturbed tropical forests: implications for ecological evaluations of land-use change, Insect Conservation and Diversity 10 (2017) 94-106. https://doi.org/10.1111/icad.12206. [7] S. Boonrotpong, S. Sotthibandhu, C. Pholpunthin, Species composition of dung beetles in the primary and secondary forests at Ton Nga Chang Wildlife Sanctuary, ScienceAsia 30 (2004) 59-65. https: // doi.org/10.2306/scienceasia1513-1874.2004.30.059. [8] S. Boonrotpong, S. Sotthibandhu, C. Satasook, Species turnover and diel flight activity of species of dung beetles, Onthophagus, in the tropical lowland forest of peninsular Thailand, Journal of Insect Science 12 (77) (2012). https://doi.org/10. 1673/031.012.7701. [9] A.J. Davis, J.D. Holloway, H. Huijbregts, J. Krikken, A.H. Kirk-Spriggs, S.L. Sutton, Dung beetles as indicators of change in the forests of northern Borneo, Journal of Applied Ecology 38 (2001) 593-616. https://doi.org/10.1046/j.1365-2664.2001.00619.x. [10] K. Frank, M. Hülsmann, T. Assmann, T. Schmitt, N. Blüthgen, Land use affects dung beetle communities and their ecosystem service in forests and grasslands, Agriculture, Ecosystems & Environment 243 (2017) 114-122. [11] T.A. Gardner, M.I.M. Hernández, J. Barlow, C.A. Peres, Understanding the biodiversity consequences of habitat change: the value of secondary and plantation forests for neotropical dung beetles, Journal of Applied Ecology 45 (2008) 883-893. https://doi.org/10.1111/j.1365-2664. 2008.01454.x. [12] L. Hayes, D.J. Mann, A.L. Monastyrskii, O.T. Lewis, Rapid assessments of tropical dung beetle and butterfly assemblages: contrasting trends along a forest disturbance gradient, Insect Conservation and Diversity 2 (2009) 194-203. https://doi.org/ 10.1111/j.1752-4598.2009.00058.x. [13] I. Quintero, T. Roslin, Rapid recovery of dung beetle communities following habitat fragmentation in central Amazonia, Ecology 12 (2005) 3303-3311. https://doi.org/10.1890/04-1960. [14] Shahabuddin, C.H. Schulze, T. Tscharntke, Changes of dung beetle communities from rainforests towards agroforestry systems and annual cultures in Sulawesi (Indonesia), Biodiversity and Conservation 14 (2005) 863-877. https://doi.org/10.1007/s10531-004-0654-7. [15] K. Vulinec, Dung beetle communities and seed dispersal in primary forest and disturbed land in Amazonia, Biotropica 34 (2002) 297-309. https:// doi.org/10.1111/j.1744-7429.2002.tb00541.x. [16] K. Vulinec, J.E. Lambert, D.J. Mellow, Primate and dung beetle communities in secondary growth rain forests: implications for conservation of seed dispersal systems, International Journal of Primatology 27 (2006) 855-879. https://doi.org/10. 1007/s10764-006-9027-2. [17] E. Nichols, T. Larsen, S. Spector, A.L. Davis, F. Escobar, M. Favila, K. Vulinec, Global dung beetle response to tropical forest modification and fragmentation: a quantitative literature review and meta-analysis, Biological Conservation 137 (2007) 1-19. https://doi.org/10.1016/j.biocon.2007.01.023. [18] R. Clements, N.S. Sodhi, M. Schilthuizen, K.L.Ng. Peter, Limestone karsts of Southeast Asia: imperiled arks of biodiversity, BioScience 56 (2006) 733-742. https://doi.org/10.1641/0006-3568(2006)56[733:LKOSAI]2.0.CO;2. [19] M. Schilthuizen, T.S. Liew, B.B. Elahan, I. Lackman-Ancrenaz, Effects of karst forest degradation on pulmonate and prosobranch land snail communities in Sabah, Malaysian Borneo, Conservation Biology 19 (2005) 949-954. https://doi.org/10.1111/j.1523-1739.2005.00209.x. [20] C. Costa, V.H.F. Oliveira, R. Maciel, W. Beiroz, V. Korasaki, J. Louzada, Variegated tropical landscapes conserve diverse dung beetle communities, PeerJ 5 (2017). https://doi.org/10. 7717/peerj.3125. [21] R.P. Salomão, D. González-Tokmana, W. Dáttilo, J.C. López-Acosta, M.E. Favila, Landscape structure and composition define the body condition of dung beetles (Coleoptera: Scarabaeinae) in a fragmented tropical rainforest, Ecol. Indic. 88 (2018) 144-151. https://doi.org/ 10.1016/j.ecolind.2018.01.033. [22] R.C. Campos, M.I.M. Hernández, Dung beetle assemblages (Coleoptera, Scarabaeinae) in Atlantic forest fragments in southern Brazil, Revista Brasileira de Entomologia 57 (2013) 47-54. [23] E. Nichols, Fear begets function in the ‘brown’ world of detrital food webs, Journal of Animal Ecology 82(4) (2013) 717-720. https://doi.org/ 10.1111/1365-2656.12099. [24] Tixier, J.M.G. Bloor, J.-P. Lumaret, Species-specific effects of dung beetle abundance on dung removal and leaf litter decomposition, Acta Oecologica 69 (2015) 31-34. https://doi.org/10. 1016/j.actao.2015.08.003. [25] P.M. Farias, L. Arellano, M.I.M. Hernández, S.L. Ortiz, Response of the copro- necrophagous beetle (Coleoptera: Scarabaeinae) assemblage to a range of soil characteristics and livestock management in a tropical landscape, Journal of Insect Conservation 19 (2015) 947-960. https://doi.org/10.1007/s 108 41-015-9812-3. [26] D.C. Osberg, B.M. Doube, S.A. Hanrahan, Habitat specificity in African dung beetles: the effect of soil type on the survival ofdung beetle immatures (Coleoptera: Scarabaeidae), Tropical Zoology 7 (1994) 1-10. https://doi.org/10.1080/03946975. 1994.10539236. [27] E. Andresen, S. Laurance, Possible indirect effects of mammal hunting on dung beetle assemblages in Panama, Biotropica 39 (2006) 141-146. https://doi.org/10.1111/j.1744-7429.2006.00239.x. [28] H. Enari, S. Koike, H. Sakamaki, Influences of different large mammalian fauna on dung beetle diversity in beech forests, Journal of Insect Science 13(54)(2013).https://doi.org/10.1673/031.013. 5401. [29] A. Estrada, D.A. Anzuras, R. Coastes-Estrada, Tropical forest fragmentation, howler monkeys (Alouatta palliata) and dung beetles at Los Tuxtlas, Mexico, American Journal of Primatology 48 (1999) 353-362. [30] C.A. Harvey, J. Gonzalez, E. Somarriba, Dung beetle and terrestrial mammal diversity in forests, indigenous agroforestry systems and plantain monocultures in Talamanca, Costa Rica, Biodiversity and Conservation 15 (2006) 555-585. https://doi.org/10.1007/s10531-005-2088-2. [31] K.V. Nguyễn, T.H. Nguyễn, K.L. Phan, T.H. Nguyễn, Bản đồ sinh khí hậu Việt Nam, Nhà xuất bản Đại học Quốc gia, Hà Nội, 2000. [32] E.J. Sterling, M.M. Hurley, M.D. Le, Vietnam–a natural history, Yale University Press, New Haven, CT, 2006. [33] T. Do, Characteristics of karst ecosystems of Vietnam and their vulnerability to human impact, Acta Geologica Sinica 75 (2001) 325-329. [34] V.T. Thái, Thảm thực vật rừng Việt Nam, Nhà xuất bản Khoa học và kỹ thuật, Hà Nội, 1978. [35] P.G.d. Silva, M.I.M. Hernández, Spatial patterns of movement of dung beetle species in a tropical forest suggest a new trap spacing for dung beetle biodiversity studies. PloS ONE 10 (5) (e0126112) (2015). https://doi.org/10.1371/journal.pone.0126112. [36] V.B. Bui, K. Dumack, M. Bonkowski, Two new species and one new record for the genus Copris (Coleoptera: Scarabaeidae: Scarabaeinae) from Vietnam with a key to Vietnamese species, European Journal of Entomology 115 (2018) 167-191. https://doi.org/10.14411/eje.2018.016. [37] V.B. Bui, M. Bonkowski, Synapsis puluongensis sp. nov. and new data on the poorly known species Synapsis horaki (Coleoptera: Scarabaeidae) from Vietnam with a key to Vietnamese species. Acta Entomologica Musei Nationalis Pragae 58 (2018) 407-418. https://doi.org/10.2478/aemnp-2018-0032. [38] O.N. Kabakov, A. Napolov, Fauna and ecology of Lamellicornia of subfamily Scarabaeinae of Vietnam and some parts of adjacent countries: South China, Laos, and Thailand, Latvijas Entomologs 37 (1999) 58-96. [39] J.E. Brower, J.H. Zar, C.N. Von-Ende, Field and laboratory methods for general ecology, 4th ed. Boston, WCB. McGraw-Hill, 1998. [40] R Core Team, R: A Language and Environment for Statistical Computing. https://www.R-project.org/ (accessed 15 May 2017). [41] J. Oksanen, F.G. Blanchet, M. Friendly, R. Kindt, P. Legendre, D. McGlinn et al., Vegan: Community Ecology Package, R package version 2.4–5 (2017). https://cran.r-project.org/web/packages/vegan. [42] R. Clements, P.K.L. Nga, X.X. Lub, S. Ambu, M. Schilthuizen, C.J.A. Bradshaw, Using biogeographical patterns of endemic land snails to improve conservation planning for limestone karsts, Biological Conservation 141 (2751e2764) (2008). https://doi.org/10.1016/j.biocon.2008.08.011. [43] P.K.L. Ng, D. Guinot, T.M. Iliffe, Revision of the anchialine varunine crabs of the genus Orcovita Ng & Tomascik, 1994 (Crustacea: Decapoda: Brachyura: Grapsidae), with descriptions of four new species, Raffles Bulletin of Zoology 44 (1996) 109-134. [44] P.K.L. Ng, Cancrocaeca xenomorpha, new genus and species, a blind troglobitic freshwater hymenosomatid (Crustacea: Decapoda: Brachyura) from Sulawesi, Indonesia, Raffles Bulletin of Zoology 39 (1991) 59-73. [45] V. Balthasar, Monographie der Scarabaeidae und Aphodiidae der Palaearktischen und Orientalischen Region. Coleoptera: Lamellicornia. Band 1. Allgemeiner Teil, Systematischer Teil: 1. Scarabaeinae, 2. Coprinae (Pinotini, Coprini). Verlag der Tschechoslowakischen Akademie der Wissenschaften, Prag, 1963. [46] Y. Hanboonsong, K. Masumoto, T. Ochi, Dung beetles (Coleoptera, Scarabaeidae) of Thailand. Part 5. Genera Copris and Microcopris (Coprini), Elytra 31 (2003) 103-124. [47] D. Král, J. Rejsek, Synapsis naxiorum sp. n. from Yunnan (Coleoptera: Scarabaeidae), Acta Societatis Zoologicae Bohemicae 64 (2000) 267-270. [48] D. Král, Distribution and taxonomy of some Synapsis species, with description of S. strnadi sp. n. from Vietnam (Coleoptera: Scarabaeidae), Acta Societatis Zoologicae Bohemicae 66 (2002) 279-289. [49] T. Ochi, M. Kon, Notes on the coprophagous scarab beetles (Coleoptera, Scarabaeidae) from Southeast Asia (IV). A new horned species of Microcopris from Vietnam and a new subspecies of Copris erratus from Peleng off Sulawesi, Kogane 5 (2004) 25-30. [50] T. Ochi, M. Kon, H.T. Pham, Five new taxa of Copris (Coleoptera: Scarabaeidae) from Vietnam and Laos, Giornale Italiano di Entomologia 15 (64) (2019) 435-446. [51] T. Ochi, M. Kon, H.T. Pham, Two new species of Copris (Copris) (Coleoptera: Scarabaeidae) and a new subspecies of Phelotrupes (Sinogeotrupes) strnadi Král, Malý & Schneider (Coleoptera: Geotrupidae) from Vietnam, Giornale Italiano di Entomologia 15 (63) (2018) 159-168. [52] J. Zídek, S. Pokorný, Review of Synapsis Bates (Scarabaeidae: Scarabaeinae: Coprini), with description of a new species, Insecta Mundi 142 (2010) 1-21. [53] H.F. Howden, V.G. Nealis, Observations on height of perching in some tropical dung beetles (Scarabaeidae), Biotropica 10 (1978) 43-46. https://doi.org/10.1111/j.1752-4598.2009.00058.x. [54] T.H. Larsen, A. Lopera, A. Forsyth, Understanding trait-dependent community disassembly: Dung beetles, density functions, and forest fragmentation, Conservation Biology 22 (2008) 1288-1298. https://doi.org/10.1111/j.1523-1739.2008.00969.x. [55] S.B. Peck, A. Forsyth, Composition, structure, and competitive behaviour in a guild of Ecuadorian rain forest dung beetles (Coleoptera; Scarabaeidae), Canadian Journal of Zoology 60(7) (1982) 1624-1634. https://doi.org/10.1139/z82-213.